Optogenetics: Novel Tools for Controlling Mammalian Cell Functions with Light - Toshihiro Kushibiki; Shinpei Okawa; Takeshi Hirasawa; Miya Ishihara (International Journal of Photoenergy)
In optogenetics, targeted illumination is used to control the functions of cells expressing exogenous light-activated proteins. Adoption of the optogenetic methods has expanded rapidly in recent years. In this review, we describe the photosensitive channel proteins involved in these methods, describe techniques for their targeting to neurons and other cell types both within and outside the nervous system, and discuss their applications in the field of neuroscience and beyond. We focus especially on the channelrhodopsin protein ChR2, the photosensitive protein most commonly employed in optogenetics. ChR2 has been used by many groups to control neuronal activity, both in vitro and in vivo, on short time scales and with exquisite anatomical precision. In addition, we describe more recently developed tools such as opsin/G protein-coupled receptor chimeric molecules and a light-activated transgene system. In addition, we discuss the potential significance of optogenetics in the development of clinical therapeutics. Although less than a decade old, optogenetics is already responsible for enormous progress in disparate fields, and its future is unquestionably bright.